Developing a Geoinformatic-engineering Stability Modeling Method, using Field Data and GIS Environment: A Case Study from Al Qarara Area in Wadi Musa, Jordan - Al Farajat, Mohammmad; Diabat, Abdullah; Al Hassanat, Hussein; Ibweni, Mohammad; Shawaqfeh, Jamal (Geological Agency, 2015)
DOI:10.17014/ijog.2.1.1-21By applying detailed geological field surveys, the spatial factors affecting geo-engineering stability were used to develop a geo-engineering stability modeling method to identify areas under potential threat of landsliding. The factors affecting geo-engineering stability in Al Qarara area in Petra-Jordan were studied and given assumed rates of importance, where optimization process was run by lag iterations; the produced spatial layers of the different factors were gathered and modeled using GIS; a final stability map was produced using an optimized equation. The produced map was validated qualitatively and quantitatively, where a comparison was made between the reality in the field and several maps of different equation. The modeling method which was developed in the context of this study proved to be suitable to produce micro-zonation maps of areas having landslide risk. Further applications on the method in other areas suffering landslides will further improve it.